Effect of substantial competent team on training after ERP implementation, continual system improvement, department related to decision support and business performance- A study of critical success factors on implementation of ERP systems among process in - SHRIVASTAVA, DR. ROOPAL (The journal of contemporary issues in business and government, 2021)
The current research focused on estimating critical success factors that are substantial competent team, training after ERP implementation, continual system improvement, department related to decision support and business performance. The respondents chosen for the current research were employees of process industries in India who are working under ERP platform. Researcher formulated four research objectives and four research hypotheses and the sample size for the current study was 139. The researcher formulated one predictor variable being substantial competent team and three predicted variables as training after ERP implementation, continual system improvement, department related to decision support and business performance. The impact between predictor variable and predicted variables were positive and significant except substantial competent team and continual system improvement which were negative but significant. Organizations may concentrate more on continual system improvement as critical success factor to increase productivity after implementation of ERP systems at department level.